Preparation method of boron nano material

Through high-temperature smelting and immersion treatment of boron nanomaterials, the complex and cost-effective production methods of boron nanomaterials in the prior art are solved, and the preparation of boron nanomaterials with high purity and standard morphology is realized, and the morphology and performance of nanotubes are adjusted by controlling the raw material ratio.

CN119683641APending Publication Date: 2025-03-25KUNMING UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411896415.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

There is a lack of simple and economical production methods in the prior art to prepare high-quality boron nanomaterials, and the shape and performance of boron nanotubes are difficult to control, which affects practical applications.

Method used

By using aluminum-boron, aluminum-titanium intermediate alloy and pure aluminum to configure the raw materials, and adding refining agent coated with aluminum foil, high-temperature smelting and soaking treatment, the content of boron and smelting conditions are controlled to form nanoboro clusters and tubular structures.

Benefits of technology

The preparation of boron nanomaterials with high purity and standard morphology can be realized, and the shape and performance of nanotubes can be adjusted by controlling the raw material ratio, which is suitable for different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683641A_ABST
    Figure CN119683641A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a boron nano material, and relates to the technical field of metallurgy and chemical industry. According to the method, aluminum boron, an aluminum-titanium intermediate alloy and pure aluminum are subjected to a high-temperature smelting reaction in a smelting furnace, and then the boron nano material can be obtained in an alloy system through an acid leaching method; the adopted raw materials are aluminum boron, aluminum titanium intermediate alloy and pure aluminum which are commonly used in the industry, and are low in cost and easy to obtain; the synthesized boron nano material is high in purity and standard in morphology, and can be tubular, sheet-shaped, cage-shaped, angular and the like; the preparation method is non-toxic and can be used for batch industrial production; due to unique physical and chemical properties, the boron nano material has wide application potential in the fields of reinforced composite materials, thermal management, radiation shielding, biomedicine, energy storage, high-temperature structural materials, optical application and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a boron nano material, and belongs to the technical field of metallurgy and chemical engineering. Background Art

[0002] Nanostructured materials, referred to as nanomaterials, refer to materials whose structural units are between 1 nanometer and 100 nanometers in size. Nanostructures are a new system constructed or created according to certain rules based on nanoscale material units. They include nanoarray systems, mesoporous assembly systems, and thin film mosaic systems. Common nanomaterials include carbon nanotubes, graphene, fullerene, and nanocomposites. These nanomaterials have a wide range of applications in electronics, energy, medicine, environment, and consumer products due to their unique properties.

[0003] Boron is a unique material with a complex structure. It has the advantages of high hardness, low density, high melting point (above 2000℃), etc. It has electron-deficient properties, so boron has a variety of allotropes, and in any case, it is composed of large-sized unit cells composed of several atoms. The structure is complex. There are currently six known crystalline variants, which are composed of icosahedrons or icosahedral fragments composed of boron atoms combined in different ways. Due to the unique properties of boron, boron nanomaterials have been widely studied while carbon nanomaterials are developing. In the past few decades, various types of boron nanomaterials have been experimentally synthesized, such as nanoclusters, nanosheets, nanowires, and nanotubes, which produce fascinating physical and chemical properties. In 1966, Olempsk et al. reported the synthesis of boron whiskers and boron needles by hydrogen reduction of boron trichloride at 1300-1800°C; from 1998 to 1991, Komatsu et al. synthesized boron films, whiskers, ribbons and sheets of boron nanomaterials by various methods; in recent years, one of the hot topics in the research of nano-boron materials is to grow boron atoms evaporated by physical means on Ag (111) under ultra-high vacuum conditions, and experimentally realize a single-atom two-dimensional boron layer, namely borobenzene.

[0004] In the development history of nanomaterials, boron exists in them more in the form of doping, and there are few related studies on pure boron nanomaterials; Patent application No. 201410152050.1 mentions a method for preparing boron nitride nanotubes, which uses cheap boron oxide powder instead of B as a boron source, and prepares nanotubes after processing and ball milling with metal magnesium powder, and prepares pure phase high aspect ratio boron nitride nanotubes in a vertical induction heater in an ammonia atmosphere; Patent application No. 202011607360.X discloses a method for preparing boron carbide nanoparticles, which uses a mixture obtained by mixing a boron source, a carbon source and an additive to prepare a slurry, heats and dries the mixture under an HCl atmosphere to obtain a dry mixture, and then heats the dry mixture under an inert atmosphere to obtain a boron carbide powder.

[0005] Before the 21st century, research on boron nanotubes was mainly in the theoretical research stage, predicting their unique structure and properties; in 2004, Ciuparu et al. used a mixed gas of BCl3 and H2 (volume ratio of about 1:6) as a boron source and a mesoporous silica template as a catalyst by magnesium substitution method to synthesize pure boron single-walled nanotubes by CVD; Liu et al. used a mixture of B2O3 and boron powder (mass ratio of 4:3) as raw materials, reacted under high temperature solid phase reaction conditions of 1000-1200°C for 4 hours, and synthesized boron nanotubes with a diameter of 10-40nm and an average length of several microns on ferrosoferric oxide nanoparticles with a diameter of less than 10nm.

[0006] In recent years, boron nanomaterials have been widely used in hydrogen storage, batteries, catalysis, electronics, superconductors, etc., and there are many theoretical calculations to predict their performance. They have strong chemical stability and high-temperature stability and have broad application prospects. However, there is currently little research and a lack of relatively simple and economical production methods. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing boron nanomaterials, which uses aluminum boron, aluminum-titanium master alloy and pure aluminum to prepare raw materials, and adds a refining agent coated with aluminum foil. The coating effect is to facilitate placement and ensure safety. The method specifically comprises the following steps:

[0008] (1) First, place the crucible into a melting furnace for preheating, put pure aluminum into the crucible, heat it to the melting temperature, wait for the pure aluminum to be completely melted, then add aluminum boron and aluminum titanium master alloy, and wait for them to be completely melted.

[0009] (2) After the step (1) is completely melted, add a refining agent wrapped in aluminum foil, stir, let stand, and keep warm; after the insulation is completed, pour out the upper layer of the melt first, and cool the remaining part to form an alloy block before taking it out.

[0010] (3) The alloy block taken out in step (2) is placed in concentrated hydrochloric acid for soaking, and then washed and filtered with deionized water to remove impurities, thereby obtaining a boron nanomaterial.

[0011] Preferably, the weight proportions of aluminum boron, aluminum titanium master alloy and pure aluminum in step (1) of the present invention are: 150-950 g of aluminum boron master alloy, 50-500 g of aluminum titanium master alloy and 0-800 g of pure aluminum in 1 kg of raw material.

[0012] The titanium in the aluminum-titanium master alloy of the present invention is mainly used for sedimentation and aggregation, and the content does not need to be too high. Preferably, the titanium in the aluminum-titanium master alloy of the present invention accounts for 0.5-5% of the total raw material mass.

[0013] The aluminum-boron master alloy of the present invention uses different contents of Al-3B, Al-8B, etc., and the addition amount is different. Preferably, the boron content accounts for 0.5-30% of the total raw material mass (referring to the total mass of pure aluminum and aluminum-boron, aluminum-titanium master alloy). The content is related to the shape of the boron nanotubes. When the content is 0.5-1%, it is cage-shaped, a little flaky and angular. When the content is 1-30%, a tubular shape will appear. The higher the content, the more tubular materials are synthesized and the larger the average size.

[0014] Preferably, the resistance furnace preheating condition in step (1) of the present invention is 150-250° C., and the preheating time is 20-40 minutes.

[0015] Preferably, the melting temperature in step (1) of the present invention is 700-1200°C.

[0016] Preferably, the mass percentage of the refining agent added in step (2) of the present invention is 5‰, which has the function of removing impurities and preventing oxidation; the stirring time is 1 to 5 minutes, and the insulation (standing) time is 1 to 5 hours. The standing process can make titanium and boron settle to the lower layer, thereby improving the preparation efficiency.

[0017] Preferably, the acid immersion solution in step (3) of the present invention is concentrated hydrochloric acid, and the immersion time is 20 to 30 hours.

[0018] The principle of the present invention is as follows: the present invention obtains the target nano-boron microstructure by controlling the process conditions of the smelting process, controls the appropriate boron content in the aluminum melt, and under the appropriate smelting temperature and holding time range, the interaction between aluminum and boron can make boron aggregate to form nano-boron clusters (sheet-shaped, angular-shaped, cage-shaped, tubular), and since the effect of boron on titanium is stronger than that of aluminum, adding an appropriate amount of titanium can make the formed nano-boron aggregate around titanium without destroying the structure of the nano-boron, and since the density of titanium is greater than that of aluminum, the nano-boron can be promoted to settle to the lower layer area during the standing process, which is beneficial to the subsequent separation; after the sedimentation, the mixture can utilize the fact that boron does not react with acid, while aluminum and titanium can be dissolved in acid, and the introduced aluminum and titanium will remain in the solution after being dissolved by acid leaching, and the solid obtained by filtration is the boron nano-material.

[0019] The beneficial effects of the present invention are:

[0020] Currently, there are relatively few synthetic technologies for obtaining nano-scale boron materials, and the synthetic methods have problems such as difficulty in controlling product size and morphology, low yield, high cost, and environmental pollution. The synthesized boron nanomaterials of different shapes will show different properties, which will have a great impact on their actual use.

[0021] (1) The raw materials used in the method for synthesizing boron nanomaterials are commonly used intermediate alloys in industry and are reasonably priced; the synthesized materials are of high purity and standardized morphology; the method is non-toxic and can be scaled up for mass production.

[0022] (2) This method can control the morphology of boron nanotubes by controlling the ratio of raw material alloys, thereby exhibiting different properties and characteristics. For example, boron nanotubes have good conductivity, and boron nanosheets have good flexibility and high specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the device of the present invention;

[0024] Figure 2 This is a microscopic structure diagram of boron nanomaterials obtained by simulation calculation in the present invention.

[0025] Figure 3 is a SEM image of the material in the aluminum-boron alloy prepared in step (2) of Example 1 of the present invention;

[0026] Figure 4 This is the EDS diagram of the aluminum-boron alloy prepared in step (2) of Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0028] Example 1

[0029] like Figure 1 As shown, the method for preparing boron nanomaterials by high-temperature melting of pure aluminum, aluminum boron and aluminum-titanium master alloy as raw materials comprises the following steps:

[0030] (1) Weigh 667 g of Al-3B (boron accounts for 2% of the total raw material mass percentage), 60 g of Al-10Ti master alloy (titanium accounts for 0.6% of the total raw material mass percentage), and 273 g of pure Al, a total of 1 kg; then weigh 5 g of refining agent and wrap it with aluminum foil.

[0031] (2) First, place a graphite clay crucible into a melting resistance furnace and heat it to 250° C., preheat it for 30 minutes, place the pure aluminum prepared in step (1) into the crucible, heat it to 850° C., wait for 20-30 minutes, and after the pure aluminum is completely melted, add the Al-3B and Al-10Ti master alloys prepared in step (1), and wait for another 20-30 minutes to completely melt them.

[0032] (3) After step (2) is completely melted, add 5 g of refining agent, stir for 2 min, let stand, and keep warm for 2 h. After the insulation is completed, pour out about 3 / 4 of the upper melt, and take out the remaining part after cooling.

[0033] (4) The alloy block taken out in step (3) is placed in concentrated hydrochloric acid (commercially available) and soaked for 24 hours, and then washed and filtered with deionized water to remove impurities to obtain a boron nanomaterial.

[0034] The SEM image of the alloy block obtained in this embodiment is as follows: Figure 3 As shown in the figure, the physical phases of B and Al can be seen; the corresponding EDS is as follows Figure 4 shown.

[0035] The boron nanomaterials prepared in this embodiment are mostly tubular in shape, with a few being cage-shaped, sheet-shaped and angular in shape, all of which are hollow structures.

[0036] Example 2

[0037] like Figure 1 As shown, the method for preparing boron nanomaterials by high-temperature melting of pure aluminum, aluminum boron and aluminum-titanium master alloy as raw materials comprises the following steps:

[0038] (1) Weigh 750 g of Al-8B (boron accounts for 6% of the total raw material mass percentage), 200 g of Al-10Ti master alloy (titanium accounts for 2% of the total raw material mass percentage), and 50 g of pure Al, a total of 1 kg; then weigh 5 g of refining agent and wrap it with aluminum foil.

[0039] (2) First, place a graphite clay crucible into a melting resistance furnace and heat it to 250° C., preheat it for 30 minutes, place the pure aluminum prepared in step (1) into the crucible, heat it to 850° C., wait for 20-30 minutes, and after the pure aluminum is completely melted, add the Al-8B and Al-10Ti master alloys prepared in step (1), and wait for another 20-30 minutes to allow them to completely melt.

[0040] (3) After the step (2) is completely melted, add 5 g of refining agent, stir for 2 min, let stand, and keep warm for 1 h. After the insulation is completed, pour out about 2 / 3 of the upper melt, and take out the remaining part after cooling;

[0041] (4) The alloy block taken out in step (3) is placed in concentrated hydrochloric acid and soaked for 24 hours, and then washed and filtered with deionized water to remove impurities to obtain a boron nanomaterial.

[0042] Compared with Example 1, Comparative Example 2 only differs in the ratio of aluminum boron and aluminum-titanium master alloy, and the standing and insulation time, thereby increasing the boron content in the raw material. The rest is exactly the same as Example 1. In the end, more tubular hollow boron nanomaterials can be obtained, and the average size is larger, and there are relatively fewer cage-shaped, sheet-shaped and angular ones.

[0043] Example 3

[0044] like Figure 1 As shown, the method for preparing boron nanomaterials by high-temperature melting of pure aluminum, aluminum boron and aluminum-titanium master alloy as raw materials comprises the following steps:

[0045] (1) Weigh 150g of Al-3B (boron accounts for 0.5% of the total raw material mass percentage), 500g of Al-10Ti master alloy (titanium accounts for 30% of the total raw material mass percentage), and 350g of pure Al, a total of 1kg; then weigh 5g of refining agent and wrap it with aluminum foil.

[0046] (2) First, place a graphite clay crucible into a melting resistance furnace and heat it to 150° C., preheat it for 40 minutes, place the pure aluminum prepared in step (1) into the crucible, heat it to 700° C., wait for 20-30 minutes, and after the pure aluminum is completely melted, add the Al-8B and Al-10Ti master alloys prepared in step (1), and wait for another 20-30 minutes to allow them to completely melt.

[0047] (3) After the step (2) is completely melted, add 5 g of refining agent, stir for 2 min, let stand, and keep warm for 1 h. After the insulation is completed, pour out about 2 / 3 of the upper melt, and take out the remaining part after cooling;

[0048] (4) The alloy block taken out in step (3) is placed in concentrated hydrochloric acid and soaked for 24 hours, and then washed and filtered with deionized water to remove impurities to obtain a boron nanomaterial.

[0049] This embodiment can ultimately obtain cage-shaped, sheet-shaped and angular-shaped boron nanomaterials, among which the cage-shaped boron nanomaterials are the most numerous.

[0050] Example 4

[0051] like Figure 1 As shown, the method for preparing boron nanomaterials by high-temperature melting of pure aluminum, aluminum boron and aluminum-titanium master alloy as raw materials comprises the following steps:

[0052] (1) Weigh 950 g of Al-8B (boron accounts for 7% of the total raw material mass percentage), 50 g of Al-10Ti master alloy (titanium accounts for 0.5% of the total raw material mass percentage), and 0 g of Al pure aluminum, a total of 1 kg; then weigh 5 g of refining agent and wrap it with aluminum foil.

[0053] (2) First, place a graphite clay crucible into a melting resistance furnace and heat it to 150° C., preheat it for 20 min, place the pure aluminum prepared in step (1) into the crucible, heat it to 1200° C., wait for 20-30 min, and after the pure aluminum is completely melted, add the Al-8B and Al-10Ti master alloys prepared in step (1), and wait for another 20-30 min to allow them to completely melt.

[0054] (3) After step (2) is completely melted, add 5 g of refining agent, stir for 2 min, let stand, and keep warm for 1 h. After the insulation is completed, pour out about 2 / 3 of the upper melt, and take out the remaining part after cooling.

[0055] (4) The alloy block taken out in step (3) is placed in concentrated hydrochloric acid and soaked for 24 hours, and then washed and filtered with deionized water to remove impurities to obtain a boron nanomaterial.

[0056] This embodiment can ultimately obtain a lot of tubular hollow boron nanomaterials. When the boron content is higher, the average size is larger, and the cage-shaped, sheet-shaped and angular-shaped ones are still relatively small.

Claims

1. A method for preparing a boron nanomaterial, characterized in that: The specific steps include: (1) First, place a crucible into a melting furnace for preheating, place pure aluminum into the crucible, heat it to the melting temperature, wait for the pure aluminum to completely melt, then add aluminum boron and aluminum titanium master alloy, and wait for them to completely melt; (2) After the step (1) is completely melted, a refining agent wrapped in aluminum foil is added, stirred, allowed to stand, and kept warm; after the heat preservation is completed, the upper layer of the melt is poured out first, and the remaining portion is cooled to form an alloy block and then taken out; (3) The alloy block taken out in step (2) is placed in concentrated hydrochloric acid for soaking, and then washed and filtered with deionized water to remove impurities, thereby obtaining a boron nanomaterial.

2. The method for preparing boron nanomaterials according to claim 1, characterized in that: In step (1), 1 kg of raw materials includes 150 to 950 g of aluminum-boron master alloy, 50 to 500 g of aluminum-titanium master alloy, and 0 to 800 g of pure aluminum.

3. The method for preparing boron nanomaterials according to claim 2, characterized in that: Titanium in the aluminum-titanium master alloy accounts for 0.5 to 5% of the total raw material mass.

4. The method for preparing boron nanomaterials according to claim 2, characterized in that: The boron content of aluminum-boron alloy accounts for 0.5-30% of the total raw material mass. Its content is related to the shape of the boron nanotubes formed. When the content is 0.5-1%, it is cage-shaped, with a little flake and angular shape. When the content is 1-30%, a large number of tubular shapes are formed, with a little cage-shaped, flake and angular shape.

5. The method for preparing boron nanomaterials according to claim 2, characterized in that: In step (1), the resistance furnace is preheated at 150-250° C. for 20-40 minutes.

6. The method for preparing boron nanomaterials according to claim 2, characterized in that: The melting temperature in step (1) is 700-1200°C.

7. The method for preparing boron nanomaterials according to claim 2, characterized in that: In step (2), the mass percentage of the refining agent added is 5‰, the stirring time is 1-5min, and the insulation time is 1-5h.

8. The method for preparing boron nanomaterials according to claim 2, characterized in that: The acid immersion solution in step (3) is concentrated hydrochloric acid, and the immersion time is 20 to 30 hours.

Citation Information

Patent Citations

  • Preparation method of boron nitride nano tube

    CN103922295A

  • A method for preparing boron carbide nanoparticles

    CN112573520B